Distribution of Rainfall under Teak Plantation - Buvaneswaran, C.; George, M.; Mohan, S. (Indian Forester, 2003)
Investigations carried out on stemflow, throughfall and interception in a 30-year-old Teak plantation (density 620 trees/ha) at Coimbatore Forest Division, Tamil Nadu have shown that, out of the annual rainfall of 1966.7 mm, 7.54% was accounted as stemflow and 51.20% as tbroughfall. Remaining 41.26% was accounted as interception. While maximum stemflow (8.68% of rainfall) and throughfall (56.71%) and minimum interception loss (34.61%) was recorded during the month of November; minimum stemflow (0.25% of rainfall) and throughfall (5.0%) and maximum interception (94.75%) was recorded during March, It was also found that the seasonal variation of rainfall influenced the stemflow and throughfall. Interception during South-West monsoon (June-August) was almost at par with average annual interception. But during North-East monsoon (September-November) the interception was much below the annual average. The results of the present study show that the interrelationship between rainfall, stemflow and throughfall in Teak is similar to that of broad leaved species like Shorea robusta. It was also found that the interception depends on parameters like crown form, density of the species, external structural features like bark characteristics and branching nature as well as rainfall pattern and other meteorological factors which influence the evaporation.